Направления НИОКР в области освоения ресурсов энергетической древесины - Anuchin A. S. (Priority directions of science and education development, 2017)
With the use of the Russian index of scientific citation, a number of research and development activities have been identified in the field of development of energy wood resources.
Keywords: ресурсы; энергетическая щепа; development; resources; energy chips; освоение; топливная щепа; fuel chips